2014
DOI: 10.1002/hed.23583
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic model for distant metastasis in locally advanced nasopharyngeal carcinoma after concurrent chemoradiotherapy

Abstract: The established model might be useful for predicting the risk of distant metastasis in patients with locally advanced NPC who underwent CCRT and may identify the patients' need for intensified adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Recently, several studies were conducted to stratify NPC patients into different groups based on the risk of distant metastasis to improve prognosis prediction [ 26 30 ]. For example, the study reported by Chen et al [ 28 ] included age, N category, hemoglobin level, and lactate dehydrogenase level to the prognostic model, and found that the prognostic model was useful for predicting the risk of distant metastasis in patients with locally advanced NPC. Another study by Zhang et al [ 30 ] incorporated fluor-18-fluorodeoxyglucose ( 18 F-FDG) uptake value; N category was also confirmed to be a predictor for distant metastasis in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies were conducted to stratify NPC patients into different groups based on the risk of distant metastasis to improve prognosis prediction [ 26 30 ]. For example, the study reported by Chen et al [ 28 ] included age, N category, hemoglobin level, and lactate dehydrogenase level to the prognostic model, and found that the prognostic model was useful for predicting the risk of distant metastasis in patients with locally advanced NPC. Another study by Zhang et al [ 30 ] incorporated fluor-18-fluorodeoxyglucose ( 18 F-FDG) uptake value; N category was also confirmed to be a predictor for distant metastasis in their study.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that preservation of salivary function and quality of life improves in IMRT survivors. A recent multicenter study also showed that in a multi-institutional setting, it was possible to achieve 90% local control rate excellence with IMRT as reported in single institutions [ 10 , 11 ]. Thus, IMRT has gradually been considered as the new standard RT for NPC.…”
Section: Discussionmentioning
confidence: 89%
“…These include DNA fragments containing hypermethylated promoter regions for several known tumour suppressor genes (e.g. CDH1, DAPK, and CDKN2A) 149,150 , hemoglobin and lactate dehydrogenase 151 , as well as multiple circulating cytokines including TGF-β 152 , interferon-γ 153 , and CD40-ligand 154 .…”
Section: Ebna1mentioning
confidence: 99%